Experimental and simulation study on lead-free solders and electroless nickel immersion silver surface finish - Hashim, Muhammad Syafiq (2023)
Simulation technology has come a long way in recent years technologies play an important role in revolutionising many industries including electronic industries. Thermal simulation provides deeper insights into a product’s behavior with different temperature scenarios, and the designs will be impacted by temperature changes. Knowing these outcomes enables to quickly adjust designs to achieve peak product performance. Therefore, this study aims to investigate the experimental and simulation on lead-free solders with ENIMAG finish. The PCB package's thermal distribution and total deformation were simulated using the ANSYS software. For experimental study, two low melting point of lead-free solders was used which are Sn-40Bi, Sn-4.0Zn-40Bi and Sn-3.0Ag-0.5Cu as comparison. ENIMAG/Cu was used as a substrate and was reflowed at 150°C for both Sn-40Bi and Sn-4.0Zn-40Bi lead-free solders. Then the substrate undergone isothermal aging process at 55°C for Sn-40Bi and Sn-4.0Zn-40Bi and different aging durations (250, 500, and 750 hours). The top surface and cross-sectional examination were characterised using optical microscope and scanning electron microscopy (SEM). The results revealed that both thermal distribution in steady-state and transient thermal shows temperature over the PCB surface is equilibrium and even for both reflow temperatures during reflow soldering and aging process. The temperature of the PCB becomes close to the ambient temperature at the end of the given time and high at the middle of PCB. For aging process, there was no or small deviation was observed for all parameters. The lowest temperature is recorded on the edge of the PCB in some cases, but the deviation is minor at 0.001°C. For aging process, maximum stress on the PCB is 195.59 MPa and minimum stress is 5.9326 MPa for 150°C while for 250°C is 753.51 MPa and 22.856 MPa for maximum and minimum stress, respectively. Besides, in the as-reflow condition, the IMC thickness for Sn-40Bi is thinner than Sn-4.0Zn-40Bi and SAC305 solder. Duplex IMC of (Cu,Ni)6Sn5 and (Ni,Cu)3Sn4 was detected at the interface of solder joint for all solder materials. During isothermal aging process, the IMC thickness for Sn-40Bi is maintain thinner than Sn-4.0Zn-40Bi and SAC305 solder. However, The IMC thickness is increased when the aging duration is increased for all solder materials. Moreover, the grain sizes of IMC morphology are changing to become rounder and denser when it was exposed to aging process